2018
DOI: 10.1186/s12885-018-4346-1
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib prevents cytarabine resistance in MCL, which is characterized by down-regulation of dCK and up-regulation of SPIB resulting in high NF-κB activity

Abstract: BackgroundThe addition of high-dose cytarabine to the treatment of mantle cell lymphoma (MCL) has significantly prolonged survival of patients, but relapses are common and are normally associated with increased resistance. To elucidate the mechanisms responsible for cytarabine resistance, and to create a tool for drug discovery investigations, we established a unique and molecularly reproducible cytarabine resistant model from the Z138 MCL cell line.MethodsEffects of different substances on cytarabine-sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Exogenous Cyr61 effectively reduces cytarabine-induced apoptosis through the NF-κB signaling pathway in acute lymphoblastic leukemia cells [ 22 ]. Upregulation of NF-κB is the main molecular process driving the development of cytarabine resistance in Z138 cells [ 23 ]. Cripto-1, an oncoprotein, promotes resistance to cytarabine-induced apoptosis by activating the TAK-1/NF-κB/survivin signaling pathway [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous Cyr61 effectively reduces cytarabine-induced apoptosis through the NF-κB signaling pathway in acute lymphoblastic leukemia cells [ 22 ]. Upregulation of NF-κB is the main molecular process driving the development of cytarabine resistance in Z138 cells [ 23 ]. Cripto-1, an oncoprotein, promotes resistance to cytarabine-induced apoptosis by activating the TAK-1/NF-κB/survivin signaling pathway [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that REEP1 could facilitate mitochondrial‐ER interactions, which may result in intracellular Ca 2+ overload and axonal damage, and REEP1 variants were recognized as causes of Neurological Disease like hereditary spastic paraplegia (HSP) and distal hereditary motor neuropathy (dHMN) . The third gene SPIB, encoding an ETS‐domain transcription factor, was believed to be associated with cancers especially in lymphomas . Also, Yi‐Jung et al found the SPIB may be involved in tumorigenesis in live cancer, and Wei et al reported that SPIB is expressed in invasive cancer cells in human primary lung cancer tissues.…”
Section: Discussionmentioning
confidence: 99%
“…37 The third gene SPIB, encoding an ETS-domain transcription factor, was believed to be associated with cancers especially in lymphomas. 38,39 Also, Yi-Jung et al 40 found the SPIB may be involved in tumorigenesis in live cancer, and Wei et al 41 reported that SPIB is expressed in invasive cancer cells in human primary lung cancer tissues. ALDH3B2 was widely known as a member of aldehyde dehydrogenases (ALDHs).…”
Section: Discussionmentioning
confidence: 99%
“…In analogy, the downregulation of DCK observed in MCL cells with acquired resistance to fludarabine was associated with "cross"-resistance to ara-C, gemcitabine, and cladribine [118]. Freiburghaus et al recently confirmed that the downregulation of DCK belongs to key molecular events responsible for ara-C resistance and reported that it can be prevented by treatment with the proteasome inhibitor bortezomib [119]. The downregulation of SLC29A1/hENT1 ara-C transporter and upregulation of cytidine-deaminase (that inactivates ara-C to an inactive metabolite) were detected in ara-C-resistant AML cells [65,66].…”
Section: Resistance To Nucleoside Analoguesmentioning
confidence: 99%